A Certified Mediator who Works as a Civil Servant in the Judiciary Institution - Sarip Hadaiyatullah, Syeh; Burhanuddin, Ahmad; Wisesha, Pramudya (KnE Social Sciences, 2024)
The Supreme Court of the Republic of Indonesia, in Supreme Court Regulation Number 1 of 2016 on Mediation Procedures in Court, states that to perform their duties as mediators, every mediator must participate and pass the certification training conducted by accredited certification institutions recognized or accredited by the Supreme Court. In its development, many civil servants such as lecturers or civil servants in ministries such as the Ministry of Manpower, Ministry of Public Works, and others, have registered as prospective certified mediators and many have successfully obtained certification as mediators from the Supreme Court. However, can certified mediators who are civil servants perform their profession as non-judicial mediators in the court? This study is a literature research as the data used is sourced from literature or written materials. Literature research is a series of research activities related to the study of literary data. The nature of this research is descriptive, where data is presented qualitatively. Descriptive research is intended to provide descriptions of situations or events. This research is descriptive because the results are presented in a narrative form. Since this study belongs to the category of literature research, the data sources were secondary data, obtained through the review of legal materials Legal materials can be divided into two types: primary and secondary legal materials. The results of this research indicate that civil servants, such as lecturers or civil servants in ministries such as the Ministry of Manpower, Ministry of Public Works, and others, who have been certified as mediators by accredited mediation institutions recognized by the Supreme Court, can indeed practice their profession as non-judicial mediators in the court. Keywords: mediation, mediator, Court